Efektivitas Model Pembelajaran TPS (Think Pair Share) Terhadap Hasil Belajar Pada Materi Animasi 3 Dimensi - Kholisho, Yosi Nur; Ismatulloh, Kholida; Sukandi (Lembaga Bale Literasi, 2024)
This research aims to determine the learning outcomes of students at SMKN 3 Selong in the 3 Dimensional Animation Subject for class XI Multimedia. The TPS (Think Pair Share) Learning Model is considered appropriate for contributing to improving student learning outcomes in animation learning, because in this learning model students are encouraged to work in teams with their classmates to solve problems given by the teacher. The research was carried out by looking at students' performance in completing animation assignments in accordance with the learning being taught. This research is experimental research where there is a control class as a comparison class and an experimental class which will be given treatment using the TPS learning model. The results of this research were that the initial hypothesis was accepted with students' average scores increasing compared to the previous learning model. Even though the average score increase only reached 20%, the practice of using the TPS learning model has achieved the target of improving student learning outcomes and student effectiveness in thinking to solve problems given in the LKPD distributed by the teacher.